Round table on Europe's role in Latin American development - Inter-American Development Bank. (Buenos Aires, Argentina : Inter-American Development Bank, 1962)
This publication contains the texts of statements by the panelists and extracts of comments by participants during the general discussion in the round table meeting held at the third annual meetings of the Governors.
On cover: Europe's role in Latin American development.
Statements and extracts of comments presented at the round table meeting held during the 3rd annual meeting of the Board of Governors of the Inter-American Development Bank in Buenos Aires, April 24, 1962.
gp 22/01/2019
Loans
Keywords: Investments, European; Europe; Latin America